Violence against women: addressing the victims’ issues through formal institution - Ghifar Baladdien Aziz Suwito Jati (Institute for Advanced Science, Social, and Sustainable Future, 2023)
This research discussed a critical issue in the current era, violence against women. It investigated the form of social services for victims of acts of violence provided by formal institution. This study focused on victims' issues regarding violence against women to the National Commission on Violence Against Women. This research was inspired by the implementation of Indonesia Regulation No. 65 of 2005 concerning the National Commission on Violence Against Women. For almost two decades since the regulation was implemented, this research explored the actual implementation of it, especially in this current area where gender-based violence has increased dramatically. Besides that, we critically investigated several factors that attract violence against women, i.e., law and societal patterns. This study used a qualitative method, including in-depth interviews, field observation, and content analysis through formal regulations. It also utilized the theory of regulations' implementation to ensure some aspects, i.e., communication, resources, dispositions, and the organizational structure. The results of this study showed that there is still a lack, especially in the communication aspect. Our findings implied that it could prevent society from utilizing social services provided by formal institutions to access proper justice. Currently, there is no optimal socialization conducted by the Office of the National Commission on Violence Against Women, though it already had some programs. The researcher suggests ensuring proper awareness and knowledge among citizens to make reports regarding gender-based violence is key. So, the mitigation regarding these issues can be tackled properly and inclusively.